EFL University Students' Errors in Translating Arabic Literary Texts into English - Mohammed, Afraa Abdel Gadir Ahmed (Gezira Journal of Educational Sciences and Humanities, 2019)
Translation is a branch of contrastive and applied linguistics since it is concerned with the knowledge of relations between languages and the application of this knowledge in communication. The importance of errors lies in the fact that it is  evidence of students' performance in the TL. This study aimed at investigating  the nature and the most frequent type of errors made by EFL university students in translating Arabic literary texts into English. The descriptive and analytical method was adopted for conducting the study. A questionnaire and a diagnostic test were chosen as tools for data collection. The SPSS programme (Statistical Package for Social Sciences) was used for data analysis. The statistical analysis for the results of the questionnaire showed that (81.8%) EFL lecturers strongly agreed that EFL students at university level make all kinds of errors in translating Arabic literary texts into English. All EFL lecturers strongly agreed  that the most frequent type of errors were due to syntactic, semantic and cultural differences between the two languages. The study come up with the following findings :errors are made in word order (79.9%), spelling mistakes (79.1%), choice of word (74.5%), punctuation marks, articles and references. Based on the findings, the study recommended that EFL students should be exposed to varieties of language through literary texts. The number of assignments in translating Arabic literary texts  into English should be increased. The number of the credit hours for the prescribed courses should also be increased, and a third course on translation should also be added.